2012
DOI: 10.1039/c2ob26295a
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective synthesis of tetra-substituted furans and cyclopropenes: copper(i)-catalyzed formal cycloadditions of internal aryl alkynes and diazoacetates

Abstract: A convenient Cu(I)-catalyzed cycloaddition of electron rich internal aryl alkynes and diazoacetates was discovered for the chemoselective and regioselective synthesis of tetra-substituted furans and cyclopropenes in moderate isolated yields (18-67%), and alkyne conversion (29-73%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Coleman et al also tackled the cyclopropenation of internal alkynes but using copper as the catalyst. After preliminary results showing that donor/acceptor diazo acetate reacted with 1-(pmethoxy)phenylprop-1-yne under CuI catalysis to afford tetrasubstituted cyclopropenes, 44 the authors applied the methodology to internal alkynylsylanes to yield 1silylcyclopropenes that are useful starting materials for various transition metal-catalysed transformations. 45 (1,3-Bis-(diisopropyl-phenyl)imidazole-2-ylidene) copper(I) chloride (iPrCuCl) was the catalyst of choice for the aforementioned transformation (Scheme 30, c).…”
Section: Scheme 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Coleman et al also tackled the cyclopropenation of internal alkynes but using copper as the catalyst. After preliminary results showing that donor/acceptor diazo acetate reacted with 1-(pmethoxy)phenylprop-1-yne under CuI catalysis to afford tetrasubstituted cyclopropenes, 44 the authors applied the methodology to internal alkynylsylanes to yield 1silylcyclopropenes that are useful starting materials for various transition metal-catalysed transformations. 45 (1,3-Bis-(diisopropyl-phenyl)imidazole-2-ylidene) copper(I) chloride (iPrCuCl) was the catalyst of choice for the aforementioned transformation (Scheme 30, c).…”
Section: Scheme 29mentioning
confidence: 99%
“…49 Coleman, et al tackled the reaction with the less reactive internal alkynes. 44 Using CuI as the catalyst in neat conditions, tetrasubstitued furans were obtained in moderate yields (Scheme 32, a). Also using copper, Wang et al reported the Cu(I)catalysed reaction of terminal alkynes with β-keto-α-diazoesters as a straightforward synthesis of 2,3,5-trisubstituted furans (Scheme 32, b).…”
Section: Scheme 31mentioning
confidence: 99%
“…Today, a unified selective method to prepare differently substituted cyclopropenes from diazo compounds, or other carbene sources, is still lacking, since in most cases furan contamination is observed and sometimes furan is even the major product. This fact has been illustrated in numerous recent reports, which are not going to be discussed here since the reactions did not start from isolated cyclopropenes.…”
Section: Metal-catalyzed Synthesis Of Furan Derivatives and Related C...mentioning
confidence: 68%
“…The most direct and practical routes for the synthesis of highly functionalized furans involve transition‐metal‐catalyzed [3+2] cycloaddition reactions between diazo compounds and acetylenes 10. In particular, Rh II ‐,10a–10f Cu I ‐,10g and Co II[10h] ‐catalyzed reactions between diazodicarbonyl compounds and terminal alkynes have been successfully conducted. Although a number of transition‐metal‐catalyzed reactions between diazodicarbonyl compounds and alkynes have been reported for the synthesis of substituted furans, there still remains a need for novel and improved synthetic routes for the preparation of highly functionalized diverse furans with high chemo‐ and regioselectivities under mild conditions.…”
Section: Introductionmentioning
confidence: 99%